The environmental impact of sewage and wastewater outfalls in Antarctica: An example from Davis station, East Antarctica. (15th November 2016) - Stark, Jonathan S.; Corbett, Patricia A.; Dunshea, Glenn; Johnstone, Glenn; King, Catherine; Mondon, Julie A.; Power, Michelle L.; Samuel, Angelingifta; Snape, Ian; Riddle, Martin
Abstract: We present a comprehensive scientific assessment of the environmental impacts of an Antarctic wastewater ocean outfall, at Davis station in East Antarctica. We assessed the effectiveness of current wastewater treatment and disposal requirements under the Protocol on Environmental Protection to the Antarctic Treaty. Macerated wastewater has been discharged from an outfall at Davis since the failure of the secondary treatment plant in 2005. Water, sediment and wildlife were tested for presence of human enteric bacteria and antibiotic resistance mechanisms. Epibiotic and sediment macrofaunal communities were tested for differences between sites near the outfall and controls. Local fish were examined for evidence of histopathological abnormalities. Sediments, fish and gastropods were tested for uptake of sewage as measured by stable isotopes of N and C. Escherichia coli carrying antibiotic resistance determinants were found in water, sediments and wildlife (the filter feeding bivalve Laternula eliptica ). Fish ( Trematomus bernacchii ) within close proximity to the outfall had significantly more severe and greater occurrences of histopathological abnormalities than at controls, consistent with exposure to sewage. There was significant enrichment of 15 N in T. bernacchii and the predatory gastropod Neobuccinum eatoni around the outfall, providing evidence of uptake of sewage. There were significant differences between epibiotic and sediment macrofaunal communities at control and outfall sites (<1.5 km), when sites were separated into groups of similar habitat types. Benthic community composition was also strongly related to habitat and environmental drivers such as sea ice. The combined evidence indicated that the discharge of wastewater from the Davis outfall is causing environmental impacts. These findings suggest that conditions in Antarctic coastal locations, such as Davis, are unlikely to be conducive to initial dilution and rapid dispersal of wastewater as required under the Protocol on Environmental Protection to the Antarctic Treaty. Current minimum requirements for wastewater treatment and disposal in Antarctica are insufficient to ameliorate these risks and are likely to lead to accumulation of contaminants and introduction of non-native microbes and associated genetic elements. This new understanding suggests that modernised approaches to the treatment and disposal of wastewater are required in Antarctica. The most effective solution is advanced levels of wastewater treatment, which are now possible, feasible and a high priority for installation. As a direct outcome of the study, a new advanced treatment system is being installed at Davis, effectively avoiding environmental risks. Graphical abstract: Highlights: First study to test effects of Antarctic Treaty (AT) minimum required WWT discharge. Non-native bacteria are introduced to coastal ecosystems from wastewater discharge. Antibiotic resistance genes were found in seawater, sediment, bivalves, urchins. Abnormal histopathology found in fish organs consistent with exposure to wastewater. AT minimum requirements will cause environmental impacts at most Antarctic stations.